Postgraduate Students' Experience of Using a Learning Management System to Support Their Learning: A Qualitative Descriptive Study - Simen A. Steindal RN, PhD, professor; Mari O. Ohnstad RN, MNSc; Ørjan Flygt Landfald MSc; Marianne T. Solberg RN, PhD, associate professor; Anne Lene Sørensen RN, MNSc, associate professor; Hege Kaldheim RN, MNSc; Cathrine Mathisen RN, MNSc; Vivi L. Christensen RN, PhD, associate professor (SAGE Publishing, 2021)
Introduction Educational institutions worldwide have implemented learning management systems (LMSs) to centralise and manage learning resources, educational services, learning activities and institutional information. LMS has mainly been used by teachers as storage and transfer of course material. To effectively utilise digital technologies in education, there is a need for more knowledge of student experiences with digital technology, such as LMSs and especially regarding how LMSs can contribute to student engagement and learning. Objective This study aimed to gain knowledge about postgraduate nursing students' experiences with the use of LMS in a subject in an advanced practice nursing master's programme. Methods A qualitative method with a descriptive design was employed. Two focus group interviews were performed with eight postgraduate nursing students from an advanced practice nursing programme at a university college in Norway. Data were analysed using qualitative content analysis. Results Three themes emerged from the data material: 1) A course structure that supports learning; 2) LMS tools facilitate preparation, repetition and flexibility; and 3) own responsibility for using the LMS for preparation before on-campus activities. Conclusion The course structure within the LMS seemed to be important to enhance postgraduate students' ability to prepare before on-campus activities. Implementation and use of LMS tools can facilitate preparation, repetition and flexibility, especially when postgraduate students study difficult topics. Postgraduate students seem to have different views regarding their own responsibility for using the LMS to prepare before on-campus activities.